(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God who rescued us with the light of knowledge from the darkness of ignorance, and guided us through clairvoyance from falling into the blindness of misguidance, and appointed for us from the law of our master Muhammad, may God’s prayers and peace be upon him, the highest knowledge and clearest indication, and may prayers and peace be upon our master Muhammad, may God’s prayers and peace be upon him, and his good and pure family, and his honorable companions, and their followers and those who He followed them, followed their path, followed their path, and adhered to their guidance until the Day of Judgment.And yet:When the researcher begins his journey by searching for the subject of his research, he makes every effort to choose one of two topics: the first: a new topic that has not been preceded by it, and the second is a topic in which he was ambiguous. We researched this from the second type, not the first, S,